STRATEGI DIGITAL MARKETING UNTUK MENINGKATKAN KEPUASAN JAMA'AH UMROH DI ALMAIDA TOUR & TRAVEL, SUKABUMI - Hikmat Purnama; Sahny Fitria Handini; Ilham Tajul Akbar; Imam Naufal Saifuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The role of digital marketing in the Umrah travel industry is growing steadily alongside the expansion of the middle class, rising religious devotion among the public, and technological advancements. This study aims to analyze digital marketing strategies for enhancing the satisfaction of Umrah pilgrims at Almaida Tour & Travel in Sukabumi. The research employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and document analysis. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that Almaida Tour & Travel’s digital marketing strategies are implemented through the integration of various digital channels, namely a website, social media (Instagram and TikTok), video marketing, and WhatsApp Group-based communication. The website serves as an information hub and conversion point, offering convenience and transparency in services; social media functions as a platform to build interaction and trust through visual content and testimonials; while video marketing plays a role in reinforcing the emotional and spiritual aspects of the pilgrims. Meanwhile, WhatsApp Groups function as a direct communication medium that enhances responsiveness and service intimacy. Additionally, the application of the Segmentation, Targeting, and Positioning (STP) strategy demonstrates alignment between market characteristics, target consumers, and the brand image built by the company.